The Relationship Between Work Factors And Turnover Intentions Among Oil And Gas Employees In Uae - M. Abudaqa, Anas M. (2021)
issue of higher employee turnover. In this regard, various factors are playing their crucial role and creating complexity for the business firms as well. In the competitive market of UAE, various public and private organizations are facing the issue of job turnover which needs an immediate solution. The study focuses on employee turnover intention in oil and gas sector of UAE in relation to the effect of several organizational factors. For this purpose, present research has undertaken for getting the reason behind employees' intention for leaving their workplaces for other companies. This has seen that UAE has high rate for employees’ job satisfaction whereas this region has high employee turnover rate as well. Using quantitative research method, a sample of 400 questionnaires were distributed among the targeted respondents of Oil and Gas companies in the UAE with a final and usable response rate of 74.50 percent. For analyzing the data, partial least square (PLS)- structural equation modeling (SEM) approach was employed to analyze the data. The findings of the study show that factors like job burnout, job satisfaction, emotional intelligence, appreciative leadership, Employee Commitment, and quality of work life are positively and significantly impacting on turnover intention of the employees. Additionally, it is observed that significant and moderating effect of appreciative leadership between emotional intelligence and turnover intention, and between quality of work life and turnover intention exists.